Reflecting on success in trauma research: experiences from the SGCNS and SIR studies. Issue 2 (2nd June 2020) - Bentley, Conor; Cooper, L; Foster, M; Fallowfield, J
Abstract : The inclusion of British Service Personnel (SP) lacking capacity into research studies from the point of injury through to medium-term rehabilitation had not previously been undertaken until work to support operations in Afghanistan (2001–2014). The Surgeon General's Casualty Nutrition Study and the Steroids and Immunity from Injury through to Rehabilitation Study sought to address the nutrition, endocrine and immune responses in a military patient cohort. A fundamental part of research is to feedback to patients, their relatives and ward staff on data collection and outcomes, and how future research may be improved to better support both injured SP and trauma patients in the UK. This paper will provide an experiential view on the delivery, operations and infrastructure requirements that should be considered when developing military research at a role-3 facility, before, during and after a study.